Formulation and characterization of a novel fluoride-releasing dental composite - Xu, X.; Ling, L.; Wang, R.; Burgess, O.J.
Objectives. The aims of this study were to formulate a novel fluoride-releasing dental composite and to evaluate its mechanical properties, fluoride release and recharge capabilities, water sorption and solubility. Methods. A fluoride-releasing dimethacrylate monomer containing a ternary zirconium fluoride chelate was synthesized. Three experimental fluoride-releasing composites were fabricated with different monomer formulas (wt.
Keywords: FLUORIDE RELEASE; RECHARGE; MONOMER; METAL CHELATE; DENTAL COMPOSITES; MECHANICAL PROPERTIES; WATER SORPTION; SOLUBILITY